Exposing the Religious Characters of the Malays in the 19th Century: A Symbolic Analysis of the Manuscript of Syair Burung - Roza, Ellya; Pama, Sindi Ayudia; Erni, Sukma; Pama, Violeta Inayah; Murni, Murni (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2022)
This article is focused on analising the religious character of the Malays in the 19th century in the Syair Burung manuscripts. It was one of the cultural relics of the Malay community in the past that can provide useful information for the religious life of today's society. This paper was based on library research with a qualitative method approach that leads to content analysis, while the primary source is the text edition of Syair Burung manuscript. The results of the analysis found that Syair Burung is a symbolic poem that uses various birds for the storyteller. This is because the Malay people were colonised by the British, thus, they did not dare to write the truth. Likewise, regarding the religious life that occurs in society, the author is only able to change the character of the story. This research found the religious character of the Malays in the 19th century was divided into a three-character group. First, a group that understands religious teachings and was obedient in practicing them, was symbolised by 13 species of birds. Second, a group that comprehends religious teachings but does not practice them, which is symbolised by 8 types of birds. Third, the group does not understand religious teachings and also does not practice them, which is symbolised by 9 types of birds.